2015
DOI: 10.1007/s10815-015-0471-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between FXIII and β-fibrinogen genes and women with recurrent spontaneous abortion: a meta- analysis

Abstract: Our meta-analysis demonstrates that the FXIII Val34Leu polymorphism has a close association with RSA and women who carry the Val allele for the FXIII Val34Leu polymorphism could have a protective effect against RSA. However, no association is detected between β-fibrinogen -455G/A polymorphisms and the risk of RSA. Future well-designed studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Overall, most studies failed to find the meaningful association of different genetic models of β-fibrinogen 455G/A (rs1800790) polymorphism with RPL, especially in the Asian and Caucasian subgroups. [ 35 36 37 ] This could be attributed to gene-gene interaction, gene-environment interaction, or other β-fibrinogen polymorphisms that may mask β-fibrinogen gene function. These results were in contrary to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, most studies failed to find the meaningful association of different genetic models of β-fibrinogen 455G/A (rs1800790) polymorphism with RPL, especially in the Asian and Caucasian subgroups. [ 35 36 37 ] This could be attributed to gene-gene interaction, gene-environment interaction, or other β-fibrinogen polymorphisms that may mask β-fibrinogen gene function. These results were in contrary to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no ethnicity and age matching were considered between two case and control groups in the former study. Li et al in a meta-analysis of 12 assays which had been performed on the association of β-fibrinogen-455G/A polymorphism and risk of RPL among Asian and Caucasian populations, no significant difference was found between case and control groups [23]. Al-Astal et al could not find any association between FGB -455G/A polymorphism and RPL risk among Palestinian women—they calculated the frequency of A and G alleles as 17.6% and 82.4% among RPL patients, which is close to our results and could be a further support of our findings [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FGB -455G/A polymorphism may have a role in increasing serum fibrinogen level and subsequent coagulation and thrombosis formation in the pathogenesis of RPL [28]. Although the association of FGB -455G/A polymorphism with RPL has been found to be meaningless in most of the studies, a combination of it with other thrombophilic variants was shown to be significant [23]. In addition, -455G/A polymorphism has been demonstrated as a significant gene variant associated with ischemic strokes in various studies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Factor II prothrombin (PTm) G20210A mutation plays an important role in RPL [17]. Coagulation factor XIII and β fibrinogen are both important for the coagulation of blood and a meta-analysis that was performed revealed that only FXIII Val34Leu polymorphism had an association with RPL [26].…”
Section: Thrombophilic Factorsmentioning
confidence: 99%